Efek Penambahan SCES Pada Sistem Multimesin dengan Damping dan Kontroler Berdasarkan Metode Critical Trajectory - Ardyono Priyadi; Nazila Iyyaya Fariha; Talitha Puspita Sari; Vita Lystianingrum; Margo Pujiantara; Sjamsjul Anam (Jurnal FORTECH, 2020)
The system can maintain its synchronization under a transient condition. The transient stability system can be evaluated using the critical trajectory method by calculating the Critical Clearing Time (CCT). The advantage of using a critical trajectory method is that the CCT can be found directly and more accurate than the time domain simulation method. This paper proposed the addition of Supercapacitor Energy Storage (SCES) and damping to enhance the transient stability on multi machine system. SCES is an electrical energy storage device that quickly stores and supplies large amounts of electricity, while damper winding damp the oscillations during unstable steady state conditions. Within the addition of SCES and damping in the system, the stability will last longer than before. The stability system is seen by the extended CCT. Furthermore, multi-machine to infinite bus used to validate the proposed method. The test system also includes the Automatic Voltage Regulator (AVR) and the governor